Eugenics in American Political Life - O'Brien, Shannon Bow. author. (orcid)0000-0002-2991-3343 Link aut Link
XIX, 125 p. 1 illus.
Keywords: The book explores the development of the American eugenics movement and how it still plays a role in American life. Building on a brief overview of the concept of eugenics, Shannon Bow O’Brien charts the foundations of the ideas, significant influences, and influencers of the movement in the last 19th and early 20th centuries. She discusses how these ideals and social life shaped American culture and encouraged attitudes toward racial and ethnic biases, including immigration policies in that period. O’Brien examines how the founding of the United States of America was built on unwanted individuals from the United Kingdom; transported felons and indentured servants were many of the original colonists. As the population forged its new nation, many of these individuals were the focus of restrictive immigration policies that sought to amend the identity of the American citizen and sought to define acceptable roles for Black persons within American society. Faithful slave monuments provided physical models to help engrain these roles within American life. O’Brien traces the development of the Mammy statue movement and its intersectionality with the restrictive immigration laws. Finally, she turns to the rhetoric of Donald Trump and contextualizes his speech in the ideology of the superiority of White Nordic nativism within American life. Shannon Bow O’Brien is Associate Professor of Instruction at the University of Texas at Austin in the Government Department. She is the author of Why Presidential Speech Locations Matter: Analyzing Speechmaking from Truman to Obama and Donald Trump (Palgrave Macmillan, 2018) and Donald Trump and the Kayfabe Presidency: Professional Wrestling Rhetoric in the White House (Palgrave Macmillan, 2020). .